OPTIMALISASI NILAI-B SEISMIK DI WILAYAH JAWA MELALUI PEMODELAN OK1993 BERBASIS VORONOI - Styawan, Yudha (Engineering Faculty Universitas Lampung, 2025)
The spatial variation of b-values in seismically active regions provides critical insight into the stress state and rupture potential of fault systems. This study focuses on the Java region and surrounding subduction zones, where detailed mapping of b-values remains uncertain despite high seismic risk. A Voronoi-based ensemble modelling framework is implemented, incorporating the Ogata-Katsura 1993 (OK1993) formulation and spatial sampling via Sobol sequences to ensure uniform partitioning. Earthquake data from 1995 onward were compiled and harmonized into moment magnitude (Mw) using conversion equations from the Indonesian Earthquake Source and Hazard Map 2017. The OK1993 model enables estimation of b-values optimized via trust-constr and initialized with maximum likelihood estimates. The results reveal that high b-values (b > 1.2) dominate offshore southwest Lampung and south of Bali, whereas low b-values (b < 0.8) appear parts of the Sumatra fault near the Sunda Strait, faults across Java, and thrusts north of Bali and Lombok. Moderate b-values (0.8–1.0) extend along the southern Java trench and may represent partially coupled megathrust segments. Interestingly, the low b-value zones may indicate locked asperities and potential seismic gap segments, especially along southern Java, where large ruptures have not occurred in recent decades. This study demonstrates the utility of spatially adaptive, data-driven approaches in capturing complex tectonic segmentation and supports their integration into future seismic hazard assessments in Indonesia, particularly in Java and its surrounding regions.